Skeletal system as a rare metastatic site in patients with ovarian carcinoma. Issue 8 (7th August 2021) - Ak, Naziye; Minareci, Yagmur; Saip, Pinar
Abstract : Objective: To evaluate the frequency and predictors of bone metastasis in patients with ovarian cancer and to determine prognostic factors associated with this finding. Methods: Patients diagnosed with ovarian cancer between January 2009 and December 2019 were evaluated. Patients with radiologically or pathologically confirmed bone metastasis were included in the study. Survival was analyzed using Kaplan-Meier curves and compared using the log-rank test. Multivariate analysis of prognostic factors related to survival was performed using the Cox proportional hazards model. Results: Nineteen (2.6%) of 736 patients had bone metastases. Patients with clear cell histology had a higher risk of bone metastases than patients with the other epithelial histology groups (12.3% vs 2.1%, p<0.001). Overall survival was significantly lower in patients diagnosed with bone metastasis at the time of cancer diagnosis than in those diagnosed with bone metastasis during the course of the disease (median 63 vs 6.1 months, p<0.001). However, when the survival time after the development of bone metastasis was examined, no difference was found between patients with metastasis at the time of diagnosis and at the time of first or later progression (median 13.6 vs 4 months, p=0.09). In addition, the median survival of patients with clear cell histology after bone metastasis did not differ statistically from that of patients with other epithelial histology (median 22 vs 7.5 months; p=0.13). In the clear cell subgroup, bone metastasis was an independent prognostic factor for survival after multivariate analysis. For all patients, the stage at diagnosis and serum CA125 and alkaline phosphatase levels at the time of bone metastasis were prognostic factors for survival. Discussion: Bone metastasis is rare in patients with ovarian cancer. However, the risk of bone metastasis is highest in patients with clear cell histology.